PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK KOSMETIK YANG MENGANDUNG BAHAN BERBAHAYA DALAM JUAL BELI ONLINE (E-COMMERCE) - Dian Sera Fauzela (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
The basic human desire to look attractive causes the cosmetic industry to continue to grow. The development of the cosmetics industry is increasing rapidly with the existence of internet media that presents e-commerce. This condition is exploited by certain individuals who wish to gain greater profits by selling dangerous cosmetics through e-commerce. The purpose of writing scientific journals is to understand legal protection for consumers against the existence of dangerous cosmetics in e-commerce, the factors that influence people to buy cosmetics using online buying and selling services and factors that influence the circulation of dangerous cosmetics in society. The method used in this research is normative legal method. The results obtained in this study are the permitting process and law enforcement carried out by the government to prevent the existence of dangerous cosmetics. The factors that influence people to buy cosmetics using e-commerce are saving time and effort, ease of transaction, completeness of information, price comparison and availability of products at any time. Meanwhile, the factors that influence the circulation of dangerous cosmetics in society are the low level of public education, people who are easily tempted by low prices and the mindset of people who like instant results.